Clinical profiles of atrial fibrillation patients with or without malignancy: analysis from the Jordan Atrial Fibrillation study. (14th October 2021) - Hamam, I; Hammoudeh, A; Jarrad, I; Abdulelah, Z; Khamis, A; Amro, M; Alhaddad, I; Tabbalat, R; Salhab Altamimi, T; Khatib, A
Abstract: Introduction: Atrial Fibrillation (AF) is the most prevalent arrhythmia and is associated with high morbidity and mortality. Malignancy can predispose to AF directly or through adverse effects of certain chemotherapeutic agents. Moreover, AF in the presence of malignancy is a special subgroup with high risk of both thromboembolism and bleeding. Purpose: To study the clinical characteristics of AF in patients with malignancy compared to those without malignancy in a Middle Eastern population. Methods: A total of 2015 Consecutive adult patients with previously or newly diagnosed AF in 19 hospitals and 30 out-patient cardiology clinics were enrolled in the Jordan AF study from May 2019 to October 2020. Clinical and epidemiological characteristics of patients with coexisting malignancy were compared to those without malignancy. Results: Of the 2015 patients enrolled in the study, 136 (6.7%) had a coexisting malignancy; with breast cancer being the most common type of cancer (19.8%). Patients with malignancy were older than patients without malignancy (71±10 vs 67.5±13.3 years, p=0.005) with no gender difference between the two groups. Patients with malignancy were less symptomatic compared to those without malignancy; fatigue (6.6% vs. 21.9%, p=0.ehab724.28492), dizziness (2.9% vs. 11.8%, p=0.0006) and shortness of breath (8.1% vs. 35.2%, p<0.0001). Patients with AF and malignancy were more likely to have permanent AF at presentation compared to patients without malignancy (42.6% vs. 29.4%, P=0.0005). While mean CHA2DS2-VASc in patients with malignancy was similar to those without malignancy (3.8±2.0 vs 3.5±2.0 p=0.269), the malignancy group had a higher proportion of patients with CHA2DS2-VASc score >2.0 compared to those without malignancy (91.9% vs. 84.8%, p=0.023). On the contrary, patients without malignancy had higher proportions with HAS-BLED score >3 compared to patients with malignancy (19.6% vs. 11.0%, p=0.014). Left ventricular hypertrophy (LVH) and pulmonary hypertension (PAH) were diagnosed more frequently on echocardiography in patients with compared to those without malignancy (55.9% vs. 34.2%, p<0.0001) and (43.4 vs. 26.2%, p<0.ehab724.28498) respectively. While patients with malignancy had a lower rate of direct oral anticoagulants (DOACs) utilization compared to patients without malignancy (34.6% vs. 48.1%, p=0.002), they had a higher rate of Low molecular weight heparin (LMWH) utilization (16.2% vs. 1.3%, p<0.0001). There was no difference in the utilization of vitamin K antagonist between the two groups (29.4% vs. 31.8%. p=0.568). Conclusion: Middle Eastern patients who have AF and coexisting malignancy were older, had less symptoms at presentation, and higher prevalence of permanent AF than patients without malignancy. These patients were more likely to be prescribed LMWH and less likely to receive DOACs compared to those without malignancy. Prospective long-term follow-up and outcomes is underway. Funding Acknowledgement: Type of funding sources: None.